The study of thermal transfer value for medium scale mixed development in Singapore / Jeffrey Ng - Jeffrey, Ng (2012)
Energy usage for building is very significant and has been on the climb from year to year especially with the growing number of buildings to cope with the development and ever growing population. With the usage of air conditioning in most buildings nowadays contributing up to 40% of total building energy use in most countries, it is becoming worrying and measure need to be taken to tackle this effect. In Singapore, studies have shown the total energy use for cooling for a building range from 45.1% up to 73% of the total building energy usage which is even more alarming. Thus Envelope Thermal Transfer Value (ETTV) was introduced as a tool to regulate and measure the building heat gain. This dissertation proposes a methodology to utilize and generate the relationship between ETTV and Total Cooling Energy (Ec) consumption using a case study. Using a medium scale mixed development building in Singapore as case study; the ETTV value & its corresponding Ec is calculated and stimulated using Carrier’s E-20 program respectively. It was found that the ETTV value for the variation of glass used range from 39.89 W/m2 to 55.81 W/m2 with translates to 4.73% reduction in ETTV value for each 0.1 SC-Value drop for Window to Wall Ratio (WWR) of only 0.29. It was also found that each W/m2 of ETTV value increases the Ec by 0.65 kW with the selected air conditioning system with COP of 3. Although the findings are specific to the case study building, it is significant as medium scale mixed developments is the most sought after and constructed buildings in Singapore. Nevertheless with the findings, proper measures to set and review the permissible ETTV value range to ensure the energy usage of building can be managed more efficiently.